Roadmap Masa Depan Indonesia Melalui Pengaturan dan Pemanfaatan Sumber Daya Alam Kelautan Bagi Sebesar-Besarnya Kesejahteraan Rakyat - Athari Farhani (UIN Syarif Hidayatullah Jakarta, 2022)
The constitution has explicitly guaranteed Indonesia to control its natural resources which are intended for the greatest prosperity of the people. considering the potential of natural resources in the marine sector is so great for the progress and welfare of the Indonesian nation in the future, so that a clear Roadmap is needed for Indonesia, both in the regulation and utilization of natural marine resources aimed at the welfare of the Indonesian people.